2017
DOI: 10.7860/jcdr/2017/26623.10541
|View full text |Cite
|
Sign up to set email alerts
|

Association between Vascular Endothelial Markers and Carotid Intima-Media Thickness in Children and Adolescents with Type 1 Diabetes Mellitus

Abstract: Introduction: Type 1 Diabetes Mellitus (T1DM) is one of the important risk factor for cardiovascular disease. Endothelial dysfunction and increased Carotid Intima-Media Thickness (CIMT) result in cardiovascular complications. Vascular Cell Adhesion Molecule-1 (VCAM-1) and Intercellular Adhesion Molecule-1 (ICAM-1) are two adhesion molecules that are markers of early atherosclerosis and play a significant role in developing atherosclerosis. Aim:To evaluate CIMT and its association with the levels of ICAM-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…These report saturated fat intakes above recommendations and inadequate serves of fruit and vegetables 7 9. This is concerning as children and adolescents with T1D have a greater risk of overweight or obesity, dyslipidemia, atherosclerosis and cardiovascular disease 7 8 10 18–21. Specific strategies and interventions to promote dietary quality and particularly vegetable intake in children are required.…”
Section: Discussionmentioning
confidence: 99%
“…These report saturated fat intakes above recommendations and inadequate serves of fruit and vegetables 7 9. This is concerning as children and adolescents with T1D have a greater risk of overweight or obesity, dyslipidemia, atherosclerosis and cardiovascular disease 7 8 10 18–21. Specific strategies and interventions to promote dietary quality and particularly vegetable intake in children are required.…”
Section: Discussionmentioning
confidence: 99%
“…Increased CIMT was found in children with type 1 diabetes mellitus, familial hypercholesterolemia, hypertension, and metabolic syndrome. 2,4,7,25,26 Children after therapy of ALL are also at substantial risk of cardiovascular disease development in adulthood. 15,16,27 It was also confirmed that cancer childhood survivors are approx.…”
Section: Discussionmentioning
confidence: 99%
“…1 Increased CIMT was found in children with metabolic syndrome, congenital adrenal hyperplasia, obesity, type 1 diabetes mellitus, and also in childhood cancer survivors. [2][3][4][5][6][7] However, the lack of pediatric, population-based reference values makes CIMT not a widely accepted marker of subclinical atherosclerosis in youth with cardiovascular risk factors. 8 The developing cardiovascular system in children is highly susceptible to the toxic effects of chemotherapeutic agents and their administration may cause endothelial damage leading to endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Since atherosclerosis in children with FH typically presents in subclinical stage, standard diagnostic imaging methods might not be su cient. Even discreet morphological changes (thickening of intimamedia complex [IMC] evaluated with ultrasound [6,7]), may be absent while the function of the arterial wall is impaired already. This stiffening process can be assessed with applanation tonometry, with the pulse wave velocity (PWV) and augmentation index (AI) being its two common surrogates.…”
Section: Introductionmentioning
confidence: 99%